2007
DOI: 10.2478/v10004-007-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Lung Function in Asbestos Pleural Disease

Abstract: As a rule, asbestosis is a disease of workers who are occupationally exposed to inhalation of asbestos dust, leaving permanent alterations on the lung parenchyma or pleura. In our ten-year study, we investigated 318 workers with pleural asbestosis from whom we took medical history which included occupational exposure to asbestos, radiological examinations and lung function, which is mandatory for the diagnosis and the follow up of the disease. We analysed functional parameters such as forced vital capacity (FV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…There are also major differences between studies regarding the intensity of exposure because of the wide variety of tasks and occupations studied. Since only two studies [41,54] reported an estimation of exposure intensity (i.e. fibre-years), we could not explore this source of heterogeneity in subgroup or regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There are also major differences between studies regarding the intensity of exposure because of the wide variety of tasks and occupations studied. Since only two studies [41,54] reported an estimation of exposure intensity (i.e. fibre-years), we could not explore this source of heterogeneity in subgroup or regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Dement et al [6] stellten unter asbestexponierten Bauarbeitern/Isolierern von US amerikanischen Nuklearwaffenbasen eine Prävalenz der COPD von 18,7 % (OR 2,66; 95 % CI 1,46 -4,97) fest (Vergleichskollektiv 6,7 %); bei Nachweis von Pleuraveränderungen wurde in 23 % und bei Nachweis von Pleura-und Parenchymveränderungen in 32,5 % in dem auch gegenüber anderen Stäuben belasteten Gesamtkollektiv eine COPD diagnostiziert. Ausnahmen hiervon stellen bei überwiegender Verwendung nicht zeitgemäßer Lungenfunktionssollwerte die Arbeiten von Begin et al [46], Van Cleemput et al [47], Schwartz et al [25,48], Ameille et al 2010 [49], Peric et al [50] und Petrovic et al [51] dar. Schwartz et al [52] und Shih et al [53] beschrieben lediglich bei Pleurafibrose (alle Grade zusammengefasst) bzw.…”
Section: Fev 1 /Fvc Einzelner Studienunclassified
“…This review shows that long-term exposure to asbestos-containing dust leads not only to a reduction of lung volume as well as to limitations of forced expiratory flows, such as FEF 50 and FEF 75 , but also to increased frequencies of FEV 1 / FVC, and elevated airway resistance. There is evidence for significant dose-response relationships and an increase in functional changes in parallel to an increase due to the latency period.…”
mentioning
confidence: 98%
“…Die hunderttausendfache Bearbeitung solcher asbestzementhaltigen Baustoffe, zum Beispiel mit dem Trennschleifer auf Baustellen, setzte neben Asbestfasern 80-90 % granuläre Zementstäube frei[13]. Vergleichbare Verhältnisse lagen im Kfz-Bremsendienst[8,12], im Isoliergewerbe, Ofenbau usw. usw.…”
unclassified